2011
DOI: 10.1002/adma.201103634
|View full text |Cite
|
Sign up to set email alerts
|

High Magneto‐Optical Activity and Low Optical Losses in Metal‐Dielectric Au/Co/Au–SiO2 Magnetoplasmonic Nanodisks

Abstract: Metal‐dielectric Au‐Co‐SiO2 magnetoplasmonic nanodisks are found to exhibit large magneto‐optical activity and low optical losses. The internal architecture of the nanodisks is such that, in resonant conditions, the electromagnetic field undertakes a particular spatial distribution. This makes it possible to maximize the electromagnetic field at the magneto‐optically active layers and minimize it in the other, optically lossy ones.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
102
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 116 publications
(106 citation statements)
references
References 32 publications
3
102
0
1
Order By: Relevance
“…Plasmonic structures composed of a number of individual elements, for example, give rise to Fano resonance effects that induce electromagnetically induced transparency (EIT) [2][3][4][5][6][7][8]. Similar phenomena have also been found in magnetoplasmonic nanosystems [9], i.e., those sharing magnetic and plasmonic functionalities and that therefore allow a further degree of freedom, namely, the external control of the system response [10][11][12][13][14]. By an adequate design of their internal structure, it is possible to obtain configurations which provide enhanced magnetooptical (MO) activity upon plasmon resonance excitation [15][16][17][18], which allow one to probe the electromagnetic (EM) field distribution inside a metallic nanoelement [19], or which yield high MO activity and low optical losses with MO figures of merit comparable with those of garnet structures [13].…”
mentioning
confidence: 79%
See 2 more Smart Citations
“…Plasmonic structures composed of a number of individual elements, for example, give rise to Fano resonance effects that induce electromagnetically induced transparency (EIT) [2][3][4][5][6][7][8]. Similar phenomena have also been found in magnetoplasmonic nanosystems [9], i.e., those sharing magnetic and plasmonic functionalities and that therefore allow a further degree of freedom, namely, the external control of the system response [10][11][12][13][14]. By an adequate design of their internal structure, it is possible to obtain configurations which provide enhanced magnetooptical (MO) activity upon plasmon resonance excitation [15][16][17][18], which allow one to probe the electromagnetic (EM) field distribution inside a metallic nanoelement [19], or which yield high MO activity and low optical losses with MO figures of merit comparable with those of garnet structures [13].…”
mentioning
confidence: 79%
“…2 , and due to the low Co concentration, there is no noticeable difference between the three situations. All cases show two characteristic low-energy (740 nm) and high-energy (620 nm) modes of antisymmetric and symmetric nature, respectively [6,13,20], as directly concluded by the obtained relative phase between the two dipoles. The abrupt change in sign of the cosine occurs exactly at the minimum in magnitude of both dipoles.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Combining plasmonics with magneto-optics is of particular interest [2][3][4][5][6][7][8] , as it enables sophisticated control of magneto-optical material properties, which can lead to many optical devices where magnetism is applied. For example, by hybridizing ferromagnetic and noble metal materials, the magneto-optical polar Kerr effect was enhanced, which was termed 'magneto-plasmonics' 9,10 . In this realm, Temnov et al 11,12 reported plasmon interferometers, which utilized propagating surface plasmons controlled by a static magnetic field due to an adjacent ferromagnetic layer.…”
mentioning
confidence: 99%
“…In the last years, the recent advances in colloidal chemistry allowed to develop complex nanoparticles with ferromagnetic and plasmonic elements with different architectures as dimers [24], flowers [25] or core-shell structures [26][27][28] that exhibit ferromagnetic properties and surface plasmon resonances. Patterning of multilayers to form nanometric elements has been also studied, mainly in order to tune the SPR [29][30][31]. This type of structures exhibit localized surface plasmon resonance, while the ferromagnetic behavior can be tuned through the shape anisotropy.…”
Section: Introductionmentioning
confidence: 99%